2021
DOI: 10.1097/pas.0000000000001725
|View full text |Cite
|
Sign up to set email alerts
|

Pathology, Radiology, and Genetics of Interstitial Lung Disease in Patients With Shortened Telomeres

Abstract: Interstitial lung diseases (ILDs) in patients with shortened telomeres have not been well characterized. We describe demographic, radiologic, histopathologic, and molecular features, and p16 expression in patients with telomeres ≤10th percentile (shortened telomeres) and compare them to patients with telomere length >10th percentile. Lung explants, wedge biopsies, and autopsy specimens of patients with telomere testing were reviewed independently by 3 pathologists using defined parameters. High-resolution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…DSP analysis demonstrated a greater upregulation of p21 than p16 in fibroblastic foci. This is unsurprising, since recent studies have highlighted increased levels of both p16 [ 39 ] and p21 [ 34 ] in response to critically shortened telomeres, and various drivers of senescence via the p53-dependent cellular senescence pathway [ 18 ]. Other groups have been able to highlight p21-positive cells with immunofluorescence in cases of IPF [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…DSP analysis demonstrated a greater upregulation of p21 than p16 in fibroblastic foci. This is unsurprising, since recent studies have highlighted increased levels of both p16 [ 39 ] and p21 [ 34 ] in response to critically shortened telomeres, and various drivers of senescence via the p53-dependent cellular senescence pathway [ 18 ]. Other groups have been able to highlight p21-positive cells with immunofluorescence in cases of IPF [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telomere shortening is associated with cellular senescence and aging, as well as the progression of various diseases, including pneumonia [ 12 ]. Telomerase, the enzyme responsible for telomere elongation, counteracts telomere shortening by adding repeated DNA sequences to the ends of chromosomes [ 13 ]. Recent studies have shown that modulation of telomerase activity can influence immune responses, including those involved in the pathogenesis of pneumonia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with IPF have an annual decline in forced vital capacity of 130-210 mL, short telomeres caused by mutations in telomere-related genes, and forced vital capacity is reduced by an average of 300 mL per year 47 . Short telomeres are associated with increased fibrosis, histological patterns, and mortality 95 . These data support the notion that telomere function is involved in the development and progression of PF.…”
Section: Introductionmentioning
confidence: 99%